University Didactics in Virtual Environments. Experience in Social Sciences - Araya-Muñoz, Isabel (2022)
Objective. This article presents the empirical study conducted to identify the incorporation of technological means in virtual environments for teaching-learning processes of higher university education in social sciences at the National University of Costa Rica. This research is part of the academic research project titled Analysis of the principles and conditions of scientific, technological, and innovation development in teaching-learning processes in subjects from three Bachelor’s degrees in Social Sciences (Araya Muñoz y Majano Benavides (2019-2021). It is also part of the lecture titled The use of technology and application of the virtual classroom in the didactic process in university courses given at the International Learning Congress (Araya Muñoz y Majano Benavides, 2019). Methodology. The methodology is descriptive with a mixed methodological approach. Surveys are validated and applied to students and professors of the Faculty of Social Sciences (FSS), and the subject programs and institutional regulations related to the object of study are reviewed. Sources, data, and the theoretical basis are triangulated. The statistical study of validity and reliability of the data supporting the analysis is incorporated. The research context was the Faculty of Social Sciences (FSS) at the National University of Costa Rica. The study population is 220 students and 56 professors from eight schools with bachelor’s degrees at FSS. Results. The results include sufficient technological resources for learning activities. The institutional virtual classroom, Aula Virtual, offers training to users and is a strength in pedagogical processes. However, the incorporation of this resource in pedagogical mediation is limited, which shows little autonomous and collaborative work. The dependence of the student body on master classes prevails. Nevertheless, an increase in technological skills is reflected. Conclusion. It is concluded that the incorporation of technological means in didactics diversifies learning. Teachers must attend processes to strengthen their basic, technical, and technological skills to generate multiplier and innovative spaces with their peers and those who are part of their virtual teaching and learning communities.